Combined therapeutic effects of HIFU, GnRH-a and LNG-IUS for the treatment of severe adenomyosis. (1st January 2019) - Yang, Xinhua; Zhang, Xiaofei; Lin, Bin; Feng, Xiao; Aili, Aixingzi
Abstract: Objective: To evaluate the combined efficacy of high-intensity focused ultrasound (HIFU), gonadotropin-releasing hormone agonist (GnRH-a) and the levonorgestrel-releasing intrauterine system (LNG-IUS) for the treatment of severe adenomyosis. Method: Four hundred and sixty-six patients with adenomyosis admitted to the Department of Gynecology of Shanghai First Maternity and Infant Hospital underwent HIFU treatment, and then were consecutively administered with GnRH-a 1 d, 1 month and 3 months after HIFU treatment. The uterine size was then measured with ultrasound or MRI 2–4 weeks after three cycles of GnRH-a injection. The LNG-IUS was then inserted when the uterine length less than 9 cm. The visual analog scale (VAS), verbal rating scale (VRS), menstrual volume score, uterus volume, MRI, serum levels of hemoglobin and CA125 were measured at pre and 3-, 6-, 12-month post-HIFU. Results: Dysmenorrhea and menorrhagia significantly relieved after combined treatment with HIFU, GnRH-a and the LNS-IUS. The uterine volume shrank and returned to its normal size. The serum CA-125 level was reduced to the normal level after the combined treatment. Conclusions: The combined therapeutic regimen of HIFU, GnRH-a and LNS-IUS is safe, effective and efficient for curing severe adenomyosis.